Soufeng sanjie formula alleviates bone erosion in CIA mice via inhibiting RANKL/NF-κB signaling pathway and ameliorates the RA symptom in patients - Lin, Dan; Wu, Yutong; Zhu, Lizhong; Yang, Jie; Ge, Jianbin; Sun, Xiaoyan; Cai, Xueting; Ye, Juan; Pang, Zhonghua; Chen, Jiao; Hu, Chunping (Frontiers in Pharmacology, 2025)
Aim of the studySoufeng sanjie formula (SF), composed by scolopendra, scorpion, astragali radix and black soybean seed coats, is an in-hospital preparation of traditional Chinese medicine used for the treatment of rheumatoid arthritis (RA). It has been demonstrated to have a prominent effect on relieving the symptoms of collagen-induced arthritis (CIA) mice after 1 month of administration. This study aimed to evaluate the effect and mechanism of SF on ameliorating bone erosion in CIA mice and RA patients.Materials and MethodsSF or methotrexate (MTX) was administered orally to CIA mice for 3 months. The degree of ankle joint destruction, osteoclast counts, bone erosion and the expression of osteoclast-related proteins were evaluated in the ankle joints of CIA mice. Then, the inhibitory effect of SF on RANKL-stimulated osteoclast differentiation was investigated in bone marrow-derived mononuclear cells in vitro, with a focus on NF-κB signaling activation. Additionally, a preliminary clinical study was conducted to evaluate the effect of SF monitoring the serum levels of bone erosion-related factors (IL-6, IL-10, OPG and TRACP) and liver and kidney functions were monitored in RA patients.ResultsSF significantly relieved the symptoms of arthritis and ameliorated bone erosion in CIA mice after 3 months of treatment, without obvious toxicity in normal ICR mice. In addition, it decreased the number of osteoclasts and reduced the expression of cathepsin K in the ankle joints of CIA mice. In vitro experiments demonstrated that SF inhibited RANKL-induced osteoclast differentiation and reduced cathepsin K and MMP9 expression in bone marrow-derived mononuclear cells. Furthermore, SF reduced p65 phosphorylation and blocked p65 nuclear translocation. Clinical observation confirmed that SF effectively improved the clinical symptoms of RA patients and regulated the serum levels of bone erosion-related factors (IL-6, IL-10, OPG and TRACP), without obvious toxicity to the patient’s liver or kidneys.ConclusionThis study confirmed that SF effectively relieves arthritis symptoms in both CIA mice and RA patients without causing obvious toxicity to the liver or kidney. The therapeutic effects were mediated through amelioration of bone erosion by inhibiting the RANKL/NF-κB signaling pathway-mediated osteoclast differentiation.